The larvae of Amarodytes duponti (Aube (Coleoptera: Dytiscidae: Hydroporinae), with comments on Bidessini larval morphology and chaetotaxy - Michat, Mariano; Alarie, Yves (Zootaxa, 2006)
Larval morphology of the Neotropical endemic dytiscid genus Amarodytes Régimbart is investigated. All three larval instars of A. duponti (Aubé) are described and illustrated with particular emphasis on morphometry and chaetotaxy. Larvae of A. duponti share with those of other Bidessini studied in detail the absence of the primary pore ABc. Contrary to other first instar Bidessini, A. duponti characterizes by the presence of an occipital suture and the absence of pores PAj and PAk. Amarodytes duponti is related to Allodessus bistrigatus (Clark) by the presence of secondary setae on the first urogomphomere, a unique feature among the Bidessini.